Protection of drinking water resources from agricultural pressures: Effectiveness of EU regulations in the context of local realities. (1st June 2021) - Wuijts, Susanne; Claessens, Jacqueline; Farrow, Luke; Doody, Donnacha G.; Klages, Susanne; Christophoridis, Chris; Cvejić, Rozalija; Glavan, Matjaž; Nesheim, Ingrid; Platjouw, Froukje; Wright, Isobel; Rowbottom, Jenny; et al.
Abstract: Over the last decades, nutrients and pesticides have proved to be a major source of the pollution of drinking water resources in Europe. Extensive legislation has been developed by the EU to protect drinking water resources from agricultural pollution, but the achievement of water quality objectives is still an ongoing challenge throughout Europe. The study aims to identify lessons that can be learnt about the coherence and consistency of the application of EU regulations, and their effects at the local level, using qualitative expert data for 13 local to regional governance arrangements in 11 different European countries. The results show that the complexities and inconsistencies of European legislation drawn up to protect drinking water resources from agricultural pollution come forward most explicitly at local level where cross-sectoral measures have to be taken and effects monitored. At this local level, rather than facilitate, they hamper efforts to achieve water quality objectives. The upcoming revision of the Water Framework Directive (WFD) should strengthen the links between the different directives and how they could be applied at local level. In addition, a more facilitated cross-sectoral approach should be adopted to improve stakeholder networks, between institutional levels and hydrological scales, to attain policy objectives at local level. Graphical abstract: Image 1 Highlights: Nitrate and pesticides from agriculture present some of the highest risks to the quality of drinking water resources. EU legislation on the protection of drinking water resources from agriculture complex to apply consistently and coherently. Implementation would benefit from more advanced cross-referencing at the EU level. Implementation requires capacity at the regional-local level for cross-sectoral decision-making.